A multicenter, randomized, controlled trial testing the effects of acupuncture on allergic rhinitis. Issue 3 (18th December 2012) - Choi, S. M.; Park, J.‐E.; Li, S.‐S.; Jung, H.; Zi, M.; Kim, T.‐H.; Jung, S.; Kim, A.; Shin, M.; Sul, J.‐U.; Hong, Z.; Jiping, Z.; et al.
Abstract Background The aim of this study was to evaluate the efficacy and safety of acupuncture in the treatment for allergic rhinitis. Methods This study was a multicenter, randomized, parallel‐controlled study. Participants were randomized to either the active acupuncture, sham acupuncture, or waitlist groups. The active and sham acupuncture groups received acupuncture treatment three times per week for 4 weeks. In the sham group, minimal acupuncture at nonacupuncture points was used. The waitlist group did not receive any acupuncture treatment. Results Of the 238 participants, 97, 94, and 47 individuals were assigned to the active acupuncture, sham acupuncture, and waitlist group, respectively. After the treatment, the difference in the total nasal symptom score (TNSS) was significantly reduced in the active acupuncture group compared with the sham acupuncture (difference: −1.03, 95% confidence interval [CI]: −1.96, −0.09, P = 0.03) and waitlist (difference: −2.49, 95% CI: −3.68, −1.29, P < 0.0001). The active acupuncture group exhibited a significant change in the total non‐nasal symptom score (TNNSS) compared with the waitlist (difference: −0.78, 95% CI: −1.22, −0.34, P = 0.0002), but not the sham acupuncture group (difference; 0.15, 95% CI: −0.21, 0.5, P = 0.56). Both active and sham acupuncture treatments resulted in significant improvements in TNSS and TNNSS compared to baseline. Conclusion Active acupuncture showed a significantly greater effect on symptoms of allergic rhinitis than either sham acupuncture or no active treatment. The symptoms of allergic rhinitis decreased significantly after treatment in the both acupuncture and sham acupuncture groups. Acupuncture appears to be an effective and safe treatment for allergic rhinitis.